Is refugee experience in childhood a risk for poorer health in adulthood?-A Swedish national survey study. - Erica Mattelin; Amal R Khanolkar; Laura Korhonen; Jill W Åhs; Frida Fröberg (Public Library of Science (PLoS), 2023)
Studies on experiences of migration in childhood and subsequent health in adulthood report conflicting results. While there is limited research on the long-term health outcomes of refugee children as they transition into adulthood, it is often observed that refugee children experience adverse health conditions upon their arrival in the host country. We examined whether adults with a childhood refugee experience were more likely to have poorer mental health, general health, and risk-behaviours compared to non-refugee migrants and Swedish-born peers We included a nationally representative sample of 18-64-year-olds who answered the Swedish National Public Health survey in 2018 or 2020. Using official register data, we categorized individuals as: 1) refugees in childhood (<age 18 years); 2) migrants in childhood; or 3) Swedish-born. Associations between childhood status (refugee, migrant, or Swedish-born) and all outcomes in adulthood were analyzed using logistic regression. The final model was adjusted for age, sexual- and gender-minority (SGM) identity, and stratified by sex. We also analysed the above and all outcomes stratified by age (18-25, 26-64), adjusted for sex and SGM-identity. We found that a childhood refugee experience was not associated with worse self-rated general or mental health, or more risk behaviours in adulthood, compared to non-refugee migrants or Swedish-born individuals. Additionally, adults with a childhood refugee experience had lower odds of at-risk alcohol use and substance use than Swedish-born peers. In general, a childhood refugee experience was not associated with worse self-rated health or risk behaviours in adulthood when considering age and sexual- and gender-minority status.